Backward leaning during gait: An underrecognized sign in Niemann-Pick type C. (August 2022) - Mainka, Tina; Kurvits, Lille; Skorvanek, Matej; Necpal, Jan; Grofik, Milan; Ganos, Christos
Abstract: Niemann-Pick type C (NPC) is a rare but treatable lysosomal disorder with heterogeneous clinical presentations including cognitive impairment, movement disorders and vertical gaze palsy. We illustrate five cases of genetically confirmed NPC and highlight backward leaning during gait as a relevant clinical sign and a useful diagnostic clue. Highlights: NPC is a rare but treatable disorder with heterogeneous clinical presentations. Backward leaning of the trunk, pronounced during gait, is a novel clinical sign. Dystonia and impaired postural body control might contribute to its pathophysiology.